41/#564 Integrating cervical cancer screening with voluntary family planning in Mozambique: the mulher study. (4th December 2022) - Salcedo, Mila P; Osman, Nafissa; Baker, Ellen; Neves, Andrea; Rangeiro, Ricardina; Mariano, Arlete; Batware, Jean Claude; Thomas, Joseph; Carns, Jennifer; Andrade, Viviane; Carrilho, Carla; Monteiro, Eliane; et al.
Abstract : Objectives: Mozambique has one of the highest rates of cervical cancer globally. The objective of our study is to implement integrated cervical cancer screening and voluntary family planning to scale up both services. Methods: Women ages 30–49 in Maputo City and Gaza Province, Mozambique were prospectively enrolled in the study and offered integrated cervical cancer screening and/or voluntary family planning services as appropriate. Cervical screening included primary human papillomavirus (HPV) testing by self-collected or provider collected cervicovaginal samples. HPV-positive women underwent visual inspection with acetic acid (VIA) to determine eligibility for ablation (thermal ablation or cryotherapy), and if ineligible were referred for excision with loop electrosurgical excision procedure (LEEP) or cold-knife conization (CKC). Results: From January 2020 to April 2022, 7, 829 women underwent cervical screening. Median age was 37 years and 46.3% were women living with HIV (WLWH). 97% of women chose self-collection. The HPV positivity rate was 32.3% overall and 39.6% among WLWH. Of the 2, 436 HPV-positive women, 2, 153 (88.3%) returned for follow-up and treatment, including ablation (n=1988, 92.3%), LEEP (n=139, 6.5%) and CKC (n=4, 0.2%). 22 women (1.0%) were diagnosed with invasive cancer and referred to gynecologic oncology. Conclusions: Our results suggest that it is feasible to perform cervical cancer screening with primary HPV testing in low-resource settings such as Mozambique. Participants preferred self-collection and almost 90% of screen positive women completed diagnostic work-up and treatment. Further study is ongoing to determine best practices for the integration of cervical screening with voluntary family planning services in Mozambique.